East African Immigrant Children Experiences with Integration in Finnish Day-cares - Onginjo, Stephen Ochieng (My University, 2018)
The present investigation analyses critically the discursive and conceptual grounding of the experiences of East African immigrant children in the integration process in the Finnish day-cares. The literature review highlights the variables that have a cause and effect on the process of social integration for this vulnerable group in the Finnish society. The cultural misalliances between the two cultures are examined and their degree of disparities analysed through the experiences of the interviewees from the East Africa region living in Finland. The significance of language in the social integration process cannot be denied. However, multi-culturalism is critical in society and communities as individuals are bound to remember their cradle land when they grow up. In this regard, the thesis utilizes thematic analysis to portray the hegemony that exists in the Finnish culture through institutions such as the day-care and the way in which they are experienced by the vulnerable group of East African immigrant children. The empirical data is utilized to explore the experiences of East African immigrant children in Finnish day-cares, roles of parents and teachers and challenges in the social integration process. The results show the common challenges of East African parents and their eagerness to integrate into the Finnish society, a factor they consider important for the subsequent integration of their children.
Keywords: Immigrant; Integration; Language; Finnish Day-cares; East Africa; Culture; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|